Application of Semi-Fowler’s Position to Overcome Ineffective Breathing Pattern in Patients with Pleural Effusion in the Intensive Care Unit (ICU) of RSD Gunung Jati, Cirebon City - Alfiatunajihah, Fika; Syaripudin, Ahmad (INDOGENIUS, 2025)
Background & Objective: According to the World Health Organization (WHO, 2023), the number of pleural effusion cases worldwide is quite high, ranking third after lung cancer, affecting approximately 10–15 million people with 100,000–250,000 deaths annually. This study aims to apply the semi-Fowler’s position intervention to pleural effusion patients with ineffective breathing pattern problems in the Intensive Care Unit (ICU) of RSD Gunung Jati, Cirebon City. Method: This research used a case study design. The subject was one client diagnosed with pleural effusion and experiencing an ineffective breathing pattern. Data were collected using anamnesis, physical assessment, direct observation, and medical records. Result: The study showed that applying the semi-Fowler’s position for three consecutive days reduced dyspnea and decreased respiratory rate from 26x/minute to 23x/minute. Conclusion: It was concluded that the semi-Fowler’s position can reduce ineffective breathing patterns in pleural effusion patients treated in the ICU of RSD Gunung Jati, Cirebon City.